A Retrospective Claims Data Analysis on the Burden of COVID-19-Related Hospitalization in Adults at High Risk for Severe Disease Progression in Germany - Timotheus Stremel; Svitlana Schnaidt; Nicole Bihrer; Emma Fröling; Christian Jacob; Agnes Kisser (Infectious Diseases and Therapy)
Abstract Introduction Individuals at increased risk of severe coronavirus disease 2019 (COVID-19) progression have a higher probability of being hospitalized. Nirmatrelvir/ritonavir (NMV/r) is an antiviral drug aiming to prevent severe disease courses. Our study aimed to assess the resource utilization and costs of adults hospitalized for COVID-19 at high risk for severe disease progression. Methods A retrospective study was conducted using German claims data. The presence of high-risk criteria was determined through recorded diagnoses, operations, procedures, and prescriptions. Individuals at high risk for severe COVID-19 progression, primarily hospitalized for COVID-19, required a recorded diagnosis for COVID-19 and additionally a diagnosis of sepsis, pulmonary embolism, acute respiratory failure, pneumonia, or a remdesivir prescription. Patients were grouped by eligibility for NMV/r treatment (eligible, eligible with restrictions, and not eligible). The outcomes of interest were reported for the timeframe of the last dominant virus variant available in the database, i.e., Delta (June 21, 2021 to December 31, 2021). Results Of approximately 3.7 million individuals continuously observable in the database, about 60% were identified as being at high risk for severe COVID-19 progression. Among high-risk individuals, 2938 patients were primarily hospitalized for COVID-19 between June 21, 2021, and December 31, 2021, two-thirds of which were suitable for NMV/r treatment (half without restrictions). Advanced age (86.3%) and cardiovascular conditions (83.9%) were the most prevalent of the predefined risk factors. Identified patients stayed, on average, 11.3 days in hospital, with inpatient mortality of 18.9%. These COVID-19-related hospitalizations resulted in mean healthcare costs of €8728. Conclusions This study reflects the economic burden of hospitalized adult individuals with COVID-19 at high risk for severe disease progression from payer’s perspective in Germany. Our findings highlight the need to prevent severe disease courses and associated hospitalizations to relieve healthcare systems regarding costs and resource allocation.